Impact of the COVID-19 Pandemic on Kidney Diseases Requiring Renal Biopsy: A Single Center Observational Study - Hakroush, Samy; Tampe, Désirée; Korsten, Peter; Tampe, Björn (Frontiers in Physiology, 2021)
Background: The coronavirus disease-2019 (COVID-19) pandemic impacted healthcare services for kidney disease patients. Lockdown and social distancing were mandated worldwide, resulting in closure of medical services. The diagnosis of various kidney diseases may have been delayed during the COVID-19 pandemic because non-urgent tests and visits were postponed due to closure of medical services during the lockdown. Methods: We here report the impact of the COVID-19 pandemic on a total number of 209 native kidney diseases requiring renal biopsy for diagnosis in a retrospective observational study from a tertiary hospital in Germany. Results: The lockdown period in March and April 2020 primarily affected patients admitted to the normal medical ward with a compensatory increased rate of renal biopsies in the postlockdown phase. In addition, there was a shift towards more patients admitted with hemoglobinuria during the COVID-19 pandemic. This phenomenon of an increased number of patients with hemoglobinuria during the COVID-19 pandemic was specifically observed in a subgroup with hypertensive nephropathy requiring renal biopsy and associated with increased proteinuria, not attributed to the COVID-19 lockdown period itself. Conclusions: To our knowledge, this is the first report of identifying a subpopulation susceptible to closure of medical services during the COVID-19 pandemic and diagnostic delay of specific kidney diseases. Therefore, the COVID-19 pandemic should be regarded as a risk factor especially in patients with diseases other than COVID-19 primarily admitted to the normal medical ward.